Design and experimental validation of the action of small molecule-based inhibitors of the FADD protein - N. V. Ivanisenko; L. Hillert; V. A. Ivanisenko; I. N. Lavrik (Вавиловский журнал генетики и селекции)
CD95 is one of the best studied members of the death receptor family. Activation of CD95 leads to the induction of the cell death programme, apoptosis, via formation of the death-inducing signaling complex (DISC). FA DD is a key adaptor protein for the formation of the C D95 DISC and activation of caspase-8 in the receptor complex. FA DD comprises the death domain and the death effector domain (DED). The death domain is essential for the interactions of FA DD with CD95, while DED is necessary for the recruitment of procaspase-8, -10 and the protein c-FLIP into the DISC. The search for the inhibitors that would block the interactions of FA DD with the other core proteins of the DISC is essential for the studies of the structure and function of this complex, investigation of the apoptosis mechanisms and development of new treatments for neurodegenerative diseases. In the course of this work, the screening for small inhibitors in silico that selectively interact with DED has been performed. For this purpose, the molecular modeling of the protein complexes and virtual screening of the potential inhibitors of FA DD has been performed. In addition, a new technology to test the activity of these inhibitors has been developed. The computational and experimental analysis performed allowed us to characterize the optimal conformation of the FA DD protein for the design of the small molecules that can bind in the region of amino acid residue Y25. We presume that further optimization of the structures of chemical compounds that can bind with the hydrophobic pocket next to the residue Y25 of FA DD will allow for the creation of the new perspective inhibitors of the programmed cell death.